What do Infertile Women Think about Oocyte Reception, Oocyte Donation, and Child Adoption? - Straehl, Juliana; Lara, Lúcia Alves da Silva; Sá, Marcos Felipe Silva de; Reis, Rosana Maria; Rosa-e-Silva, Ana Carolina Japur de Sá (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose The views of infertile couples regarding oocyte donation by third parties and adoption are unknown, as these may be interpreted as a final closure of the available options for conception. This study aimed to determine the acceptance of oocyte donation, oocyte reception, and child adoption of infertile women who submitted to assisted reproductive technology (ART) treatmentMethods Sixty-nine women who were under treatment for infertility and submitted to ART procedures were included in this cross-sectional study. They were evaluated using semi-structured questionnaires administered during ovulation induction in a treatment cycle. Marital status, religion, years of schooling, occupation, type of infertility, age, duration of infertility, number of previous ART cycles, mean oocyte number per cycle, and mean number of embryos per cycle had no influence on a woman's acceptance of oocyte donation or oocyte reception.Results More than 90% of the patients thought that the subject of “adoption” should be brought up during their ART treatments, although they preferred to discuss this topic with psychologists, not doctors. Women with occupations were more willing to consider adoption.Conclusion The opinions of these patients on these issues seem to be based on personal concepts and ethical, religious, and moral values. Women preferred to discuss adoption with psychologists rather than doctors.
Keywords: marital infertility; oocyte donation; adoption; reproduction